2022
DOI: 10.3390/brainsci12060780
|View full text |Cite
|
Sign up to set email alerts
|

CircXPO5 Plays a Neuroprotective Function in the Lateral Geniculate Nucleus of Glaucoma by Regulating GRIN2A

Abstract: Purpose: Previous studies have found the neurodegeneration and atrophy of glaucomatous lateral geniculate nucleus (LGN), but the mechanism is still unknown. Circular RNA (circRNA) plays some important roles in physiological and pathological progression of the disease. In this study, we focused on the differentially expressed circRNAs and the mechanism for circXPO5 in LGN degeneration in a macaque glaucoma model. Methods: Using RNA-seq, we analyzed the differentially expressed circRNAs in a macaque glaucoma mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…HspB5 is upregulated by several transcription factors, the most important being heat shock factor 1 (HSF1)(De Thonel et al 2012 ). Among validated target genes for miR-330-5p that might be relevant in the CNS are the NMDA receptor GRIN2A (Yan et al 2022 ) and the glial glutamate transporter GLT-1 (Li et al 2022 ). GRIN2A is known to activate the PI3K/Akt pathway under stress conditions (Wu and Tymianski 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…HspB5 is upregulated by several transcription factors, the most important being heat shock factor 1 (HSF1)(De Thonel et al 2012 ). Among validated target genes for miR-330-5p that might be relevant in the CNS are the NMDA receptor GRIN2A (Yan et al 2022 ) and the glial glutamate transporter GLT-1 (Li et al 2022 ). GRIN2A is known to activate the PI3K/Akt pathway under stress conditions (Wu and Tymianski 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lncRNAs may emerge as competing endogenous RNAs (ceRNAs) and can potentially correspond to specific messenger RNAs (mRNAs) through sponging to their target miRNAs [144][145][146]. Moreover, miRNAs can bind to their specific mRNAs and repress their expressions in the ceRNA network.…”
Section: Competing Endogenous Rnasmentioning
confidence: 99%
“…Similar to lncRNAs, circRNAs can also function as ceRNAs for miRNAs, whereby miRNAs play certain modulatory effects on mRNAs. For example, Zhichao Yan et al [146] suggested that circXPO5 and GRIN2A can act as ceRNAs and compete with miR-330-5p to reduce circXPO5, which will have beneficial effects for glaucoma patients. CeRNAs are related to the molecular mechanisms in ocular disease, such as age-related macular degeneration [151]; thus, a ceRNAs network analysis can efficiently identify molecules related to their regulation.…”
Section: Competing Endogenous Rnasmentioning
confidence: 99%